Sex work matters : exploring money, power, and intimacy in the sex industry - Ditmore, Melissa Hope; Levy, Antonia; Willman, Alys (Zed Books ; Distributed in the USA exclusively by Palgrave Macmillan, 2010)
Sex Work Matters brings together sex workers, scholars and activists to present pioneering essays on the economics and sociology of sex work.